KOMODIFIKASI POPULARITAS: STUDI NETNOGRAFI PRODUK OVERPRICE INFLUENCER DAN IMPLIKASINYA TERHADAP UMKM - Muh Riswandi; Andi Indriani Ibrahim; Az - Zahrah Diva Celia; Felicia Pavita Cendana; Cut Syaila Chaerani (LPPM Universitas Nias Raya, 2025)
The rising popularity of influencers on social media has shaped consumer behavior, including the tendency to buy overpriced products with questionable quality. This study aims to analyze public perceptions of such products promoted by influencers and their impact on Micro, Small, and Medium Enterprises (MSMEs). A qualitative netnographic approach was employed on the TikTok platform by observing public comments and user interactions. The findings reveal that while some consumers are influenced by personal branding, many express criticism over the fairness of prices. Meanwhile, MSMEs offering similar products at affordable prices struggle with limited digital exposure. These results highlight the inequality in digital marketing and the need for greater consumer awareness about product value. The study concludes that personal branding significantly influences consumption patterns, but not always in alignment with fair pricing principles.